Predictors of Breastfeeding among Women Admitted with Severe Preeclampsia before 34 Weeks - Grundy, Sara J.; Avram, Carmen M.; Dillon, Jacquelyn; Darling, Alice; Zemtsov, Gregory; Cate, Jennifer JM; Wheeler, Sarahn; Dotters-Katz, Sarah K. (American Journal of Perinatology, 2024)
Objective Patients with severe preeclampsia (sPREX) face barriers to successful breastfeeding (BF), including an increased risk of maternal and newborn complications, prematurity, and low birth weight. Patients with early-onset sPREX (before 34 weeks' gestation) may be at even greater risk, yet there are little data available on factors associated with BF challenges in this population. We describe rates of BF initiation at hospital discharge and BF continuation at postpartum (PP) visit and identify factors associated with BF noninitiation and BF cessation among patients admitted with early-onset sPREX.Study Design Retrospective cohort study of women with sPREX admitted at less than 34 weeks' gestation to a single tertiary center (2013–2019). Demographic, antepartum, and delivery characteristics were evaluated. Factors associated with BF noninitiation at maternal discharge and with BF cessation at routine PP were assessed. Patients with intrauterine or neonatal demise and those missing BF data were excluded. Bivariate statistics were used to compare characteristics and Poisson regression was used to estimate relative risks (RR).Results Of 255 patients with early-onset sPREX, 228 (89.4%) had BF initiation at maternal hospital discharge. Initiation of BF occurred less frequently among patients with tobacco use in pregnancy (7.5 vs. 37.0%, χ2, p < 0.001, RR: 0.69 [95% confidence interval, CI: 0.52–0.92]). At 6 weeks' PP, 159 of 199 (79.9%) patients had BF continuation. Maternal age under 20 years (1.9 vs. 17.5%, χ2, p = 0.01, RR: 0.36 [95% CI: 0.14–0.91]) and experiencing maternal morbidity (25.2 vs. 45.0%, χ2, p = 0.01, RR: 0.80 [95% CI: 0.66–0.96]) were associated with BF cessation at the PP visit.Conclusion Among patients with early sPREX, tobacco use in pregnancy was associated with noninitiation of BF at discharge, whereas young maternal age and maternal morbidity were associated with cessation of BF by routine PP visit. Further research is needed on how to support BF in this population, especially among patients with these associated factors.Key Points
Keywords: breastfeeding; maternal morbidity; neonatal morbidity; severe preeclampsia; prematurity; tobacco use in pregnancy